'Kinesinopathies': emerging role of the kinesin family member genes in birth defects. Issue 12 (19th May 2020) - Kalantari, Silvia; Filges, Isabel
Abstract : Motor kinesins are a family of evolutionary conserved proteins involved in intracellular trafficking of various cargoes, first described in the context of axonal transport. They were discovered to have a key importance in cell-cycle dynamics and progression, including chromosomal condensation and alignment, spindle formation and cytokinesis, as well as ciliogenesis and cilia function. Recent evidence suggests that impairment of kinesins is associated with a variety of human diseases consistent with their functions and evolutionary conservation. Through the advent of gene identification using genome-wide sequencing approaches, their role in monogenic disorders now emerges, particularly for birth defects, in isolated as well as multiple congenital anomalies. We can observe recurrent phenotypical themes such as microcephaly, certain brain anomalies, and anomalies of the kidney and urinary tract, as well as syndromic phenotypes reminiscent of ciliopathies. Together with the molecular and functional data, we suggest understanding these 'kinesinopathies' as a recognisable entity with potential value for research approaches and clinical care.